Integrative Exercise and Lifestyle Intervention Increases Leisure-Time Activity in Breast Cancer Patients. (November 2014) - Casla, Soraya; Hojman, Pernille; Cubedo, Ricardo; Calvo, Isabel; Sampedro, Javier; Barakat, Ruben
Background. Physical activity has been demonstrated to increase survival in breast cancer patients, but few breast cancer patients meet the general recommendations for physical activity. The aim of this pilot study was to investigate if a supervised integrated counseling and group-based exercise program could increase leisure-time activity in women with breast cancer. Methods . This pilot project, designed as a single-arm study with pre-post testing, consisted of 24 classes of combined aerobic and strength exercise training as well as classes on dietary and health behavior. A total of 48 women with breast cancer who were undergoing or had recently completed anticancer treatment completed the study. Leisure-time physical activity, grip strength, functional capacity, quality of life (QoL), and depression were assessed at baseline, after intervention, and at the 12-week follow-up after intervention. Results . The breast cancer patients increased their leisure-time physical activity ( P = .004), global strength ( P = .004), functional capacity ( P = .001), and QoL ( P = .009), and their depression score ( P = .004) significantly decreased. These improvements were independent of whether the patients were in ongoing therapy or had completed their treatment. Conclusion . This integrated intervention may produce lifestyle changes in breast cancer patients and survivors using the teachable moment to increase their leisure-time physical activity and, thereby, their QoL.